Compulsory medical intervention and the right to respect for private life - Rūmniece-Pakule, Katrīna (Riga Graduate School of Law, 2023)
The permissibility of compulsory and involuntary medical interventions in connection to body autonomy and the right to respect for private life has been brought to spotlight in the recent years as a result of the COVID-19 pandemic, in response to which states took various measures, including mandatory vaccination or recovery certificates. However, the importance of body autonomy and balancing the right to respect for private life under Article 8 of the European Convention on Human Rights with public interest – such as public health and the rights and freedoms of other persons – has always had relevance in jurisprudence. To address this issue, the author analyses judgments from the European Court of Human Rights and Latvian courts regarding medical interventions such as vaccines, blood and DNA tests, and forced sterilisation procedures.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law; Human rights; body autonomy; medical intervention; European Convention on Human Rights